Stabilization of Natural Rubber against the Effect of Cyclic heating at Different Temperature using Cashew Nut Shell Liquid (Technical CNSL) - Felix, Balogun Ayo (International Journal of Applied Science and Engineering (India), 2020)
Natural rubber being a polymer formed in plants has very limited usefulness if not processed further. The processed (vulcanized) rubber can be further stabilized against thermal oxidation and degradation when put to use to extend the life span. The effect of cyclic heating on natural rubber treated with cashew nut shell liquid (CNSL) was determined. The natural rubber samples were dissolved in a given di-ethyl ether and a measured quantity of paraffin was added and divided into two (2) parts. The first groups were samples without stabilizing additive while the other contains stabilizing additive blended in them. The samples were heated at 600C, 800C and 1000C over varying periods of 3, 6, 9, 12 and 15 hours respectively and the compounded dried rubber was weighed into each of 12 cavities of a locally fabricate aluminium mould and the mould and its contents introduced into the oven. A solution of a measured amount of each sample in hexane was taken for viscometric measurement. Change in viscosity with length of heating shows that the various samples were degraded with time. The level of degradation of the rubber samples treated with cashew nut shell liquid (CNSL) as stabilizer showed better thermal stability compared with those without stabilizing additive.